2019
DOI: 10.1186/s12864-019-5898-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sex determination genes and their evolution in Phlebotominae sand flies (Diptera, Nematocera)

Abstract: Background Phlebotomine sand flies (Diptera, Nematocera) are important vectors of several pathogens, including Leishmania parasites, causing serious diseases of humans and dogs. Despite their importance as disease vectors, most aspects of sand fly biology remain unknown including the molecular basis of their reproduction and sex determination, aspects also relevant for the development of novel vector control strategies. Results Using comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Findings in other insect species of sex-specific fru splicing and/or disruption of male courtship behaviors after fruM knockdown led to the hypothesis that fru ’s role as a sex-determination switch gene was highly conserved ( 14, 15, 17, 18, 20, 21, 23, 24, 59 ). This hypothesis was also supported by findings that inserting fru genes from drosophilid species with divergent courtship behaviors into D. melanogaster males recapitulated D. melanogaster behaviors, instead of phenocopying each species’ own behaviors ( 60 ), which suggested that divergence in FruM downstream targets likely contributes to specifying species-specific behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Findings in other insect species of sex-specific fru splicing and/or disruption of male courtship behaviors after fruM knockdown led to the hypothesis that fru ’s role as a sex-determination switch gene was highly conserved ( 14, 15, 17, 18, 20, 21, 23, 24, 59 ). This hypothesis was also supported by findings that inserting fru genes from drosophilid species with divergent courtship behaviors into D. melanogaster males recapitulated D. melanogaster behaviors, instead of phenocopying each species’ own behaviors ( 60 ), which suggested that divergence in FruM downstream targets likely contributes to specifying species-specific behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The primary purpose of the present work was to identify the sex-determination system, but we also did a preliminary (and unsuccessful) attempt of identification of the sex-determination gene by looking at protein-coding genes is the candidate Y-linked scaffolds. This failure is quite expected: Identifying the sex-determining gene by sequence similarity is a difficult task since it varies among Diptera families, and is unknown in many of them ( Saccone et al 2011 ; Salz 2011 ; Petrella et al 2019 ). None of the candidate protein-coding genes that were identified on the Y seem good candidates for the sex-determining gene, as they either had a premature stop codon or were otherwise incomplete genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used for the screening of genes associated with various traits in sugarcane, such as sucrose accumulation [ 39 , 40 ], smut resistance [ 41 , 42 ] and the response to low nitrogen [ 43 ]. Transcriptome analysis was also used for the identification of sex-determining genes in many insects, such as Plutella xylostella [ 44 ], Phlebotominae sand flies [ 45 ], whitefly [ 46 ], Sogatella furcifera [ 47 ] and Zeugodacus tau (Walker) [ 48 ].…”
Section: Introductionmentioning
confidence: 99%